Inter-joint coordination variability decreases during dual-task treadmill running. - Teng, Hsiang-Ling; Armour Smith, Jo (Sports Biomechanics, 2025)
This study examined the effects of dual-task (DT) running on lower extremity and trunk coordination variability and whether these effects differed across running speeds. Thirty-one asymptomatic recreational runners (18 males, 13 females; age 26.2 ± 6.9 years; BMI 23.6 ± 2.8 kg/m²) completed treadmill running trials under three task conditions: single-task (ST), DT withan easy cognitive task (DT-easy), and DT with a difficult cognitive task (DT-hard). Each condition included three speeds: 85%, 100%, and 115% of preferred speed. Coordination variability of lower extremity joints and trunk segments during stance was quantified using Vector Coding and Ellipse Area methods. Two-way repeated-measures ANOVAs showed significant main effects of task (p < 0.05), with lower coordination variability observed under DT-hard compared to ST conditions. Speed effects were also significant, with greater variability at slower speeds. No significant task-by-speed interactions were found, indicating that DT effects were consistent across speeds. These findings suggest runners exhibit reduced movement adaptability under cognitively demanding DT conditions. Evaluation and training protocols for runners may benefit from incorporating DT paradigms to better reflect real-world demands.